Diagnosing Cushing's disease in the context of chronic kidney disease: a case report and literature review. Issue 4 (October 2019) - Stroud, Anna; Zhang, John; McCormack, Ann
Abstract : Objective: The diagnosis of Cushing's disease (CD) is particularly challenging in patients with chronic kidney disease (CKD) due to abnormalities of the hypothalamo–pituitary–adrenal axis associated with the latter. This case report presents discrepant biochemical findings in a patient with CKD who was subsequently diagnosed with CD, and outlines principles which may guide the definitive diagnosis of CD in this context. Methods: The case of a patient with Stage 4 CKD who underwent transsphenoidal surgery for pituitary-dependent CD is presented. A literature review was conducted to identify similar cases and characterise features of hypothalamo–pituitary–adrenal axis dysfunction in CKD. Results: The patient discussed herein presented with markedly elevated plasma adrenocorticotrophic hormone (ACTH) due to a pituitary macroadenoma, with normal 24-h urine free cortisol (24-UFC) but abnormal overnight dexamethasone suppression testing and elevated midnight salivary cortisol. He experienced biochemical remission after undergoing transsphenoidal adenomectomy. A literature review revealed that CKD can be associated with elevated serum cortisol, reduced UFC and elevated plasma ACTH. Only four other cases of CD being diagnosed in a patient with CKD have been published. The loss of a circadian rhythm of cortisol secretion was the most common feature among all cases. Conclusions: To establish a definitive diagnosis of CD in the context of pre-existing CKD, the absence of circadian rhythms of cortisol and ACTH is a more sensitive indicator than 24-UFC and low-dose dexamethasone suppression testing.